Serum Sodium and Febrile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs)
Serum sodium determinations were studied prospectively in 69 children with febrile convulsions followed in the Department of Paediatrics, Zuiderziekenhuis, Rotterdam, the Netherlands.